PERANCANGAN IDE BISNIS TAS GITAR KULIT CUSTOM - Nicolas Hendrawan; Rendy Iswanto (Jurnal Vicidi, 2016)
Heinnick is a company that produce leather guitar’s bag that can be customized and made of genuine leather. Nowadays, manyguitarists are rising. To carry their guitar, guitarist use a bag that is widely available on the market. However, the bag’s material and shape is nearly equal. From the research, guitarist wants a guitar bag which is durable, strong, safe for guitar, customable, so the guitarist can be taken properly and safely, but still stylish and trendy, because guitar bags on the market less suitable with their wants, and not accommodate their needs.